Metal‐Ion‐Regulated Miniature DNA‐Binding Proteins Based on GCN4 and Non‐native Regulation Sites. Issue 10 (29th January 2014) - Oheix, Emmanuel; Peacock, Anna F. A.
Abstract The design of artificial peptide dimers containing polypyridine switching domains, for which metal‐ion coordination is shown to regulate DNA binding, is reported. Short peptides, based on the basic domain of the GCN4 transcription factor (GCN4bd), dimerised with either 2, 2′‐bipyridine (bipy(GCN4bd)2) or 2, 2′:6′, 2′′‐terpyridine (terpy(GCN4bd)2) linker units, undergo a conformational rearrangement on CuII and ZnII coordination. Depending on the linker substitution pattern, this is proposed to alter the relative alignment of the two peptide moieties, and in turn regulate DNA binding. Circular dichroism and UV–visible spectroscopy reveal that CuII and ZnII coordination promotes binding to DNA containing the CRE target site, but to a differing and opposite degree for the two linkers, and that the metal‐ion affinity for terpy(GCN4bd)2 is enhanced in the presence of CRE DNA. Binding to DNA containing the shorter AP1 target site, which lacks a single nucleobase pair compared to CRE, as well as half‐CRE, which contains only half of the CRE target site, was also investigated. CuII and ZnII coordination to terpy(GCN4bd)2 promotes binding to AP1 DNA, and to a lesser extent half‐CRE DNA. Whereas, bipy(GCN4bd)2, for which interpeptide distances are largely independent of metal‐ion coordination and less suitable for binding to these shorter sites, displays allosteric ineffective behaviour in these cases. These findings for the first time demonstrate that biomolecular recognition, and specifically sequence‐selective DNA binding, can be controlled by metal‐ion coordination to designed switching units, non‐native regulation sites, in artificial biomolecules. We believe that in the future these could find a wide range of applications in biotechnology.